2019
DOI: 10.1088/1741-2552/ab4c77
|View full text |Cite
|
Sign up to set email alerts
|

A versatile robotic platform for the design of natural, three-dimensional reaching and grasping tasks in monkeys

Abstract: Objective. Translational studies on motor control and neurological disorders require detailed monitoring of sensorimotor components of natural limb movements in relevant animal models. However, available experimental tools do not provide a sufficiently rich repertoire of behavioral signals. Here, we developed a robotic platform that enables the monitoring of kinematics, interaction forces, and neurophysiological signals during user-defined upper limb tasks for monkeys. Approach. We configured the platform to p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

7
2

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…The arrays implantation was achieved using a pneumatic compressor system (Impactor System, Blackrock Microsystems). A pedestal ( Pedestal A ) was then fixated to a compliant titanium mesh (Medtronic Ti-Mesh) modelled to fit the skull shape and implanted in a previous surgery a few weeks earlier 27 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The arrays implantation was achieved using a pneumatic compressor system (Impactor System, Blackrock Microsystems). A pedestal ( Pedestal A ) was then fixated to a compliant titanium mesh (Medtronic Ti-Mesh) modelled to fit the skull shape and implanted in a previous surgery a few weeks earlier 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Clinically effective systems should demonstrate the ability to enable truly functional arm movements rather than simplified tasks such as single-joint movements. Consequently, we developed a robotic platform allowing the quantification of reach and grasp movements 27 that would feel natural and unconstrained to monkeys. We trained three Macaca fascicularis monkeys to reach for, grasp, and pull an instrumented object placed on the end effector of a robotic arm ( Figure 1 ).…”
Section: Studying Natural Arm Movementsmentioning
confidence: 99%
“…To test our hypothesis, we simultaneously recorded the activity of neural populations from motor and somatosensory cortex of four monkeys as they reached for and interacted with objects 26 . Using trajectory tangling 17 , we showed that the neural population dynamics substantially differed between the two cortical regions.…”
Section: Introductionmentioning
confidence: 99%
“…Two females Macaca Fascicularis (Mk-Sa, age 7 years, weight 4 kg and Mk-Br, age 4 years, weight 3.5 kg) were trained to reach with the left arm for a spherical object, grasp it, and pull it towards a return position to receive a food reward [41]. Animals were housed within a group of five animals at the University of Fribourg, Switzerland.…”
Section: B Afferent Fiber Modelmentioning
confidence: 99%